DESIGN OF A LEARNING VIDEO ON DECORATIVE WORKS USING STILLATION TECHNIQUES FOR GRADE VIII F STUDENTS AT STATE MIDDLE SCHOOL 24, SEMARANG CITY - Putri, Rista Adelia (Universitas Negeri Semarang, 2025)
This study aims to develop a learning video media as an aid in delivering decorative work material using stylization techniques for eighth-grade students at SMP Negeri 24 Semarang City, as well as to test the feasibility of the developed media. The design of this media is motivated by the unavailability of learning media that supports learning to create decorative work using stylization techniques in stages and contextually, so that students tend to have difficulties when practicing the work. The design procedure was carried out using the Design Thinking approach, through the stages of empathize, define, ideate, prototype, and test. The final result of the media produced is a 34-minute learning video consisting of four main parts including the opening, presentation of the core material, demonstration of work, and closing. The objects used as inspiration for the work are objects from the surrounding environment and also the local potential of Semarang City. Based on the results of the feasibility test, a percentage score of 98 was obtained from material experts, and a score of 92 from media experts. Overall, the media developed in this study was declared